Comparative Evaluation of the Antidiabetic Effects of Different Parts of Cassia fistula Linn, a Southeast Asian Plant - John Wilking Einstein; Mustafa Mohd Rais; Mustafa Ali Mohd (Journal of Chemistry)
The hypoglycemic effect of the methanolic and aqueous extracts of whole parts of Cassia fistula in both normoglycemic and streptozotocin-nictotinamide induced Type 2 diabetic rats were investigated. Acute toxicity, oral glucose tolerance test and glucose uptake in isolated rat hemidiaphragm were performed in normal rats. Diabetes was induced in Sprague Dawley rats by the administration of streptozotocin-nictotinamide (50, 110 mg/kg b.w., resp.) intraperitoneally. Different extracts of Cassia was administered to diabetic rats at 250 and 500 mg/kg doses for 21 days. Biochemical parameters like blood glucose, insulin, glycosylated hemoglobin, lipid profile, and serum marker enzymes were determined. The methanolic extract of the bark and leaves were show more effective in causing hypoglycemia in normoglycemic rats. Diabetic rats showed increased levels of glycosylated hemoglobin, reduced levels of plasma insulin, were significantly reverted to near normal after oral administration of the bark and leaf methanolic extracts. Glucose uptake studies in isolated rat hemidiaphragm have shown enhanced peripheral utilization of glucose. Chronic treatment of Cassia remarkably restored the normal status of the histopathological changes observed in the selected tissues. Dose dependent anti-diabetic effects with the cohorts receiving the methanolic extract of bark followed by leaves of Cassia was revealed.